Regulation of cognition: Validation of a short scale for Portuguese first-year university students - Bártolo-Ribeiro, Rui; Peixoto, Francisco; Casanova, Joana; Almeida, Leandro (Anales de Psicología / Annals of Psychology, 2020)
The quality of learning in Higher Education is particularly dependent on students' skills in regulating their cognition. This regulation requires cognitive and metacognitive skills as well as motivational dimensions. Due to its relevance in explaining students' academic achievement and developing lifelong learning skills, it´s important to increase research in the area. This study aims to adapt and validate a short version of the Regulation of Cognition of Metacognitive Awareness Inventory to first-year Portuguese university students. A sample of 360 students was considered and was identified a three-dimensional structure (Planning, 4 items; Strategies, 7 items; and Monitoring and evaluation, 7 items) with a second-order factor (Regulation of Cognition). The internal consistency values of the reduced scale are within the acceptable parameters for a self-report scale and the correlations with academic achievement at the end of the first year of the university guarantee the predictive validity of the scale. This short version of regulation of cognition measure allows its use in research with other instruments in larger studies and can function as a diagnostic / screening tool to help students in higher education learning challenges.